A History of Russia - Dukes, P. author. aut Link
XIV, 448 p.
Keywords: In this edition of A History of Russia, Paul Dukes takes full account of the extraordinary changes that have occurred since the arrival of first Mikhail Gorbachev and then Boris Yeltsin. Substantially expanded and rewritten, this edition sets these events within the context of over 1100 years of Russian history. From Medieval Kiev and Muscovy to post-Soviet Russia, this is an invaluable work for anyone studying this remarkable country.